Democratic Experiments Problematizing Nanotechnology and Democracy in Europe and the United States - Laurent, Brice (Inside Technology, 2017)
This book looks at the democratic constructions surrounding public debates about issues related to scientific and technological development, specifically in this case nanotechnology. Brice Laurent argues that nanotechnology is a lens through which one can build a theoretical and practical approach to the study of contemporary democracies, exploring the joint production of nanotechnology itself and democratic order and identifying questions related to the exercise of citizenship, forms of national sovereignty, and channels of political legitimacy. This book helps increase visibility of and accessibility to STS methodologies for scholars and practitioners outside the field of science, technology, and society.